Short-term assays for mesenchymal stromal cell immunosuppression of T-lymphocytes - Herzig, Maryanne C.; Christy, Barbara A.; Montgomery, Robbie K.; Cantu-Garza, Carolina; Barrera, Gema D.; Lee, Ji H.; Mucha, Nicholas; Talackine, Jennifer R.; Abaasah, Isaac A.; Bynum, James A.; Cap, Andrew P. (Frontiers in Immunology, 2023)
Trauma patients are susceptible to coagulopathy and dysfunctional immune responses.Mesenchymal stromal cells (MSCs) are at the forefront of the cellular therapy revolution with profound immunomodulatory, regenerative and therapeutic potential. Routine assays to assess immunomodulation activity examine MSC effects on proliferation of peripheral blood mononuclear cells (PBMCs) and take 3-7 days. Assays that could be done in a shorter period of time would be beneficial to allow more rapid comparison of different MSC donors. The studies presented here focused on assays for MSC suppression of mitogen-stimulated PBMC activation in time frames of 24 h or less. Three potential assays were examined-assays of apoptosis focusing on caspase activation; assays of phosphatidyl serine externalization (PS+) on PBMCs; and measurement of tumor necrosis factor alpha (TNF) levels using rapid ELISA methods. All assays used the same initial experimental conditions: cryopreserved PBMCs from 8-10 pooled donors, co-culture with and without MSCs in 96-well plates, and PBMC stimulation with mitogen for 2-72h. Suppression of caspase activity in activated PBMCs by incubation with MSCs was not robust and was only significant at times after 24h. Monitoring PS+ of live CD3+ or live CD4+/CD3+ mitogen activated PBMCs was dose dependent, reproducible, robust and evident at the earliest time point taken, 2h, although no increase in the percentage of PS+ cells was seen with time. The ability of MSC in co-culture to suppress PBMC PS+ externalization compared favorably to two concomitant assays for MSC co-culture suppression of PBMC proliferation, at 72h by ATP assay, or at 96 h by fluorescently labeled protein signal dilution. TNF release by mitogen activated PBMCs was dose dependent, reproducible, robust and evident at the earliest time point taken, with accumulating signal over time. However, suppression levels with MSC co-culture was reliably seen only after 24h. Takeaways from these studies are: 1) while early measures of PBMC activation is evident at 2-6h, immunosuppression was only reliably detected at 24h; 2) PS externalization at 24h is a surrogate assay for MSC immunomodulation; 3) rapid ELISA assay detection of TNF release by PBMCs is a robust and sensitive assay for MSC immunomodulation at 24h.